2009
DOI: 10.1007/s11746-009-1393-4
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Investigation of Frying Oil Quality Using VIS/NIR Hyperspectral Analysis

Abstract: Traditional chemical methods of analyzing frying oil quality are time-consuming and not amenable to on-line measurement. The main objective of this study was to evaluate quality changes of heated oils based on visible/ near infrared spectral analysis using a hyperspectroradiometer. The reflectance spectra of the heated oils were analyzed within the range 400-1,750 nm. Acid value, total polar component, and viscosity of oil samples were used as indicators of different quality levels of oil. Partial least square… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Anderson and Walker (2003) also studied the application of on-line VIS/NIR spectroscopy to determine the fat content in ground beef stream and reported a high accuracy with standard error of prediction (SEP) of 1.00-1.68% for calibration and 2.15-2.28% for validation. Yavari, Hamedi, and Haghbin (2009) using VIS/NIR hyper-spectral analysis studied the quality of used frying oils. Near-infrared spectroscopy instruments are also recognised as effective tools for quality control in the food industry due to their fast and non-destructive measurements, there are no requirement for using hazardous reagents and solvents, and there can be more flexible sample handling.…”
Section: Introductionmentioning
confidence: 99%
“…Anderson and Walker (2003) also studied the application of on-line VIS/NIR spectroscopy to determine the fat content in ground beef stream and reported a high accuracy with standard error of prediction (SEP) of 1.00-1.68% for calibration and 2.15-2.28% for validation. Yavari, Hamedi, and Haghbin (2009) using VIS/NIR hyper-spectral analysis studied the quality of used frying oils. Near-infrared spectroscopy instruments are also recognised as effective tools for quality control in the food industry due to their fast and non-destructive measurements, there are no requirement for using hazardous reagents and solvents, and there can be more flexible sample handling.…”
Section: Introductionmentioning
confidence: 99%
“…The FFA contents of the frying oil samples ranged from 0.090 to 1.889 % and increased with heating time. Previous studies on the FFA contents of various frying oils have reported very diverse values of measurements [1,3,5,8]. These differences were explained as being due to different frying times, temperatures and oil types.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the cross validation method, higher r and lower RMSEP values were obtained by the test set validation method (Table 3). Previous studies used NIR log 1/T (first derivative and second derivative spectrum) [3,5] and reflectance spectra [8] combined with PLS techniques to predict FFA values of frying oils, and the r values were found to be more than 0.93. These differences between previous studies and this one were mainly due to variation levels and wavenumber regions used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It does not require additional reagents or solvents ). Previous studies have reported the determination of free fatty acid (FFA), total polar material (TPM) (Ng et al 2007;Gerde et al 2007), acid value (AV), and total polar compound (TPC) values (Yavari et al 2009;Ng et al 2011;Ogutcu et al 2012;Ma et al 2014) for heated oils with added water or other frying oil. These studies showed that the FFA and TPM values for heated edible and frying oils could be monitored using NIR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%